2011
DOI: 10.3168/jds.2010-3827
|View full text |Cite
|
Sign up to set email alerts
|

Attenuating effect of casein glycomacropeptide on proliferation, differentiation, and lipid accumulation of in vitro Sprague-Dawley rat preadipocytes

Abstract: Food components with the ability to suppress preadipocyte proliferation and intracellular lipid accumulation may be helpful in the prevention of obesity, which is a worldwide health concern. Casein glycomacropeptide (GMP), which has pronounced gastric inhibitory activity, could potentially possess fat synthesis inhibition properties and an obesity-alleviating capacity. The objective of the present study was to investigate the effect of GMP on the proliferation and differentiation of preadipocytes as well as tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…Previous studies showed mixed effects of milk peptides on PPARγ activation. Peptides from casein glycomacropeptides or tuna fish decreased PPARγ protein levels and lipid accumulation in primary rat and 3T3-L1 preadipocytes, respectively [42,43]. Conversely, Chakrabarti and Wu [18] showed that synthetic lactotripeptides, IPP and VPP, originally resulting from casein digestion during fermentation, upregulate PPARγ levels and lipid storage in 3T3-F442A cells.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies showed mixed effects of milk peptides on PPARγ activation. Peptides from casein glycomacropeptides or tuna fish decreased PPARγ protein levels and lipid accumulation in primary rat and 3T3-L1 preadipocytes, respectively [42,43]. Conversely, Chakrabarti and Wu [18] showed that synthetic lactotripeptides, IPP and VPP, originally resulting from casein digestion during fermentation, upregulate PPARγ levels and lipid storage in 3T3-F442A cells.…”
Section: Discussionmentioning
confidence: 98%
“…Casein glycomacropeptide (GMP), which is a casein-derived whey peptide, deserves much interest for its proposed biological activities, such as inhibiting intestinal bacterial adhesion and inhibition from binding of cholera toxin (CT) to Chinese hamster ovary (CHO)-K1 cells [ 19 , 20 ]. Our previous studies have demonstrated that GMP supplementation efficiently suppresses the proliferation, differentiation and lipid accumulation of in vitro pre-adipocytes [ 21 ]. GMP can also reduce plasma total cholesterol and slightly ameliorate the inflammatory state in obese rats [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Glycomacropeptide (GMP), a κ‐casein‐derived macropeptide f(106–169) comprised of 64 amino acids, has been reported to possess many bioactivities, such as reducing weight gain, decreasing cardiovascular disease risk markers, and improving intestinal flora . In our previous study, GMP reduces body weight of obese Sprague‐Dawley (SD) rats induced by high‐fat diet, and inhibits proliferation and differentiation of preadipocytes isolated from SD rats in vitro . Furthermore, our study shows that papain‐generated peptides from GMP suppress lipopolysaccharide‐induced inflammatory response in murine RAW 264.7 macrophages, and protect macrophages from hydrogen peroxide‐induced oxidative stress .…”
Section: Introductionmentioning
confidence: 76%